Rural public library development framework - Abu, Roziya; Rafie, Siti Khadijah; Mohamad Tanuri, Zati Atiqah; Hamzah, Mohd Faizal (Universiti Teknologi MARA, Kedah, 2017)
This rural public library development Framework is proposed as a guideline for small and rural public libraries in any country to build and maintain their physical and resources relevance, significance and prominence to the country. The elements that should be considered to develop small and rural public libraries; cultural relevance, responsive to local information needs, applicable policies, community development and infrastructure. This framework aimed to contribute knowledge and analysis in relation to community development and rural public libraries. In addition, some consideration has been given to analysis that may subsequently lead to the development of practices in relation to improvement of small and rural public library usage. There is no guideline on developing rural public libraries yet. Rural public libraries will be able to utilize this framework in order to develop library which will fulfill the community information needs.